PENGARUH PRESEPSI HARGA, KUALLITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN PT. SOYO AJI PERKASA - Ajib Catur Yudo Yuwono; Aries Setiawan; Ariati Anomsari; Ida Farida (LPPM Universitas Sains dan Teknologi Komputer, 2024)
In the context of increasingly tight business competition in the current era, both at the domestic and global levels, companies must have the ability to win the competition by ensuring customer satisfaction. This research aims to analyze the influence of Price Perception, Service Quality on Customer Loyalty mediated by Customer Satisfaction at PT. Soyo Aji Perkasa. This research used quantitative and purposive sampling methods, with 127 respondents. This research used questionnaire analysis and a literature review. The data analysis technique used in this research is path coefficient analysis and Specific Indirect Effect. With the hypothesis showing r table > t table and P value < 0.05 with the conclusion that all hypotheses have a significant positive effect.